Mineralogy and geochemistry of a clogged mining reservoir affected by historical acid mine drainage in an abandoned mining area - Valente, Teresa Maria Fernandes (2015)
The present study is focused on a water reservoir that is under the influence of AMD in the historic mining area of Riotinto (SW Spain). Transport of particulate matter and chemical precipitation within the reservoir has caused its clogging. Hydrochemical, geochemical and mineralogical characterization allowed to assess the degree of contamination by trace elements. The results indicate high average concentrations of metals and metalloids in water and sediments. The sediments are strongly enriched in As, Pb, Cu, and Zn, which occur with concentrations > 1000 mg/kg. Highest accumulation was observed for As and Pb, which gave enrichment factors in the range 358–471, indicative of extreme pollution. Geochemical trends show strong correlation between major elements, including Fe and Al, mobilized from the source material. Mineralogy of the clogging material showed a short-range of spatial variability. Among the newly formed phases jarosite and goethite are the most abundant. They are especially concentrated in the clay size fraction. Combining results about chemistry of the sediments and mineral distribution suggests that As is being retained by both clay and iron-rich minerals. Furthermore, results indicate that jarosite forms directly from sulphide oxidation, whereas goethite may result from transformations undergone in the reservoir.